Деякі форми легалізації грошових коштів та іншого майна, здобутих злочинним шляхом - Аркуша, Лариса Ігорівна; Аркуша, Лариса Игоревна; Arkusha, L. (My University, 2010)
According to the axiological approach, comparative and legal analysis of legal provision of person's moral values at the prejudicial stage of criminal procedure under the international legal norms has been researched and the directions of improving of the legal mechanism have been denoted. Moral and legal criteria of reasons, conditions and borders of limitation of person's rights to liberty and personal privacy during investigation and preventive measures, speciﬁ cally detention, have been determined.
Аркуша Л. І. Деякі форми легалізації грошових коштівта іншого майна, здобутих злочинним шляхом / Л. І. Аркуша // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 142-151.
Keywords: легалізація грошових коштів та іншого майна, здобутих злочинним шляхом; легализация денежных средств и другого имущества, полученных преступным путем; legalization of funds and other property obtained by criminal means